Human visual perception‐based localized backlight scaling method for high dynamic range LCDs. Issue 8 (8th August 2016) - Park, Jae Sung; Hwang, Insung; Cho, Nam Ik
Abstract: This paper presents a backlight control algorithm for liquid crystal display devices, which considers the human visual properties that we are usually attracted to the saliencies in a scene. The saliency means regions or objects that have different contrast or color from the surrounding, and thus attract our attention, which can be measured in various ways from each pixel value and its relation with the surrounding ones. Hence, by keeping or boosting the backlight of salient regions while suppressing in others, the quality of salient regions and overall contrast are enhanced. In addition, power can be saved by backlight dimming in non‐salient regions, without loss of overall quality in terms of human visual perception. In this backlight control process, the amount of energy consumption is regulated so that the proposed method consumes less than or equal energy as before, by developing a power management algorithm based on the bit rate control strategies of MPEG2 video encoders. Precisely, the energy consumption in each backlight unit is controlled by a parameter, so that the sum of energies of overall backlight units is kept within a limit. Abstract : We present a backlight control algorithm for liquid crystal displays, which considers the human visual properties that we are attracted to the saliencies in scenes. By boosting the backlight of salient regions while suppressing in others, the quality of salient regions and overall contrast are enhanced. The amount of energy consumption is also regulated so that the method consumes less than before.